TaN thin film study for Superconducting BEOL integration - Segaud, R.; Chene, T.; Gergaud, P.; Minoret, S.; Gustavo, F.; Garrione, J.; Royer, A.; Nemouchi, F. (Proceedings of the IEEE International Interconnect Technology Conference, 2023)
Superconducting materials integration is one of the emerging subjects for quantum applications. This paper proposes an integration scheme based on superconducting layer etching. A material selection is proposed for interconnections including metal and dielectric. Then, a focus is realised on TaN layers as a potential technological choice. The deposition process window is explored in term of N 2 flow and thickness leading to a T c up to 2 K for 40 nm of TaN.